A systematic review and meta‐analyses of food preference modifications after bariatric surgery. (26th July 2021) - Guyot, Erika; Dougkas, Anestis; Nazare, Julie‐Anne; Bagot, Sarah; Disse, Emmanuel; Iceta, Sylvain
Summary: This systematic review and meta‐analyses aimed to synthesize evidence of the link between bariatric surgery and changes in food preferences, considering the method of assessment. MEDLINE, Cochrane Library, Web of Science, Cinahl, PsychINFO, ProQuest, and Open grey were searched incorporating two blocks of terms ("Intervention" and "Food Preferences"). Interventional or observational studies involving patients (BMI ≥ 35 kg m −2 ) with sleeve gastrectomy (SG) or Roux‐en‐Y Gastric Bypass (RYGB) and a control group were included. Meta‐analyses were performed comparing the standardized daily mean percentage energy from proteins, carbohydrates, and lipids between preoperative and postoperative patients. Fifty‐seven studies concerning 2, 271 patients with RYGB and 903 patients with SG met the inclusion criteria, of which 24 were eligible for meta‐analysis. Despite a total reduction in macronutrient intakes, the meta‐analyses revealed a postoperative increase in percentage energy from proteins at 12 months (0.24, 95% CI: 0.03, 0.46, { I 2 } = 73%) and a decrease in percentage energy from fat at 1 month (−0.47, 95% CI: 0.86, 0.09, { I 2 } = 72%), up to 24 months (−0.20, 95% CI: −0.31, 0.08, { I 2 } = 0%). In conclusion, the present systematic review and meta‐analyses showed changes of food preferences in terms of macronutrient, food selection and, overall food appreciation up to 5 years following bariatric surgery.